SCREENING ASYMPTOMATIC URINARY TRACT INFECTION IN BOYS SCHOOL AGE IN TANJUNG JOHOR, PELAYANGAN, JAMBI - Miftahurahmah; Hasna Dewi; Fairuz Quzwain (Universitas Jambi, 2020)
ABSTRACT Background: Urinary Tract Infection (UTI) is a common infection in children. Prompt diagnosis and appropriate treatment are very important to reduce the morbidity associated with this condition. Rapid screening with Urine dipstick is helpful for early detection urinary tract infection. The purpose of this study to identification urinary tract infection in school age boys. Method: this was a cross sectional study. The samples were boys in elementary school without urinary tract infection sign, with presumptive UTI criteria based on dipstick examination who had positive nitrit or positive leukocyte esterase or both of them. Result: There were 126 boys with mean age 8.3 years old (6-12 years old). Boy with presumtive UTI based on dipstick found in only one case (0.8%). Most of them were underwent circumcision (90/71.4%) and have good daily habit such as washing genital area after miction (108 / 85.7%) and hand washing (108/85.7%). Conclusion: the number of UTI cases in this study was very small, most of sample were underwent circumcision and they have good daily habit. Key word: dipstick, screening, UTI